Commissioning of the MultiRad 350 cell and small animal x-ray irradiation system - Saikkonen Aleksi; Niemelä Jarkko; Sipilä Petri; Keyriläinen Jani (ELSEVIER SCI LTD, 2022)
Purpose: The main objective of this study was to commission a commercial x-ray irradiation system to be used for cell and small animal studies.
Materials and methods: Evaluated characteristics of an x-ray irradiator included dose linearity and dose repeatability with respect to time, x-ray beam profiles, light field to irradiation field agreement and absolute radiation dose. Radiochromic films, ionization chambers and radiophotoluminescence dosimeters were used for dosimetry and the maximum settings of the irradiator were applied.
Results: The dose was linear with time using several voltage settings and the dose repeatability with time was within 5% beyond 15 s of irradiation time. The x-ray beam profiles were acceptable, flatness being less than 4%. The light field to irradiation field agreement appeared to have a maximum difference of 0.5 cm; the irradiation field being closer to the irradiator's door than the light field.
Conclusions: The MultiRad 350 x-ray irradiation system can be used in a safe and controlled manner for irradiating cells and small animals. However, the user should be careful to verify the filter position prior the irradiation.